Catalytic gasification of phenol in supercritical water with Ru/graphitized carbon black. Issue 79 (9th August 2016) - Yu, Jiangdong; Guan, Qingqing; Chen, Qiuling; Ning, Ping; Gu, Junjie; Huang, Xiaodian; Shi, Yuzhen; Miao, Rongrong
Abstract : Ru/GCB was prepared for catalytic gasification of phenol in SCW, it was active and stable, CGE was maintained at a higher level than 93% in 7 consecutive runs. The aggregation of Ru particles may be responsible for the slight loss of activity. Abstract : Phenol is a long-lived intermediate, and it is ubiquitous in the supercritical water gasification (SCWG) processes of various organic materials such as biomass, lignite and sewage sludge. In this work, ruthenium supported on graphitic carbon black (Ru/GCB) was prepared for catalytic gasification of phenol in supercritical water. It exhibited excellent catalytic performance towards phenol gasification, a nearly complete gasification of phenol was achieved at a moderate temperature of 500 °C with an 1 g g −1 catalyst loading. Kinetic study indicated the activation energy and the frequency factor for phenol gasification were 154.0 ± 27.2 kJ mol −1 and 23.2 ± 4.5, respectively. Furthermore, catalyst recycling experiments were conducted to evaluate the stability of Ru/GCB catalyst in the SCWG. X-ray diffraction, Raman spectrum, N2 adsorption, X-ray photoelectron spectroscopy and transmission electron microscopy were performed to characterize the fresh and used catalyst in order to investigate possible changes of catalyst after the recycling, the results indicated that the catalyst was found to be stable for phenol gasification under the experimental conditions.